MODERNISASI DAN SEKULARISASI PEMIKIRAN ISLAM DI INDONESIA - Muhammad Zein Damanik; Dini Yuliani; Dwi Ananta Aura Ningrum; Dea Novita (Jurnal At-Tabayyun, 2023)
Modernization and secularization are two interrelated concepts in the development of Islamic thought in Indonesia. Modernization refers to efforts to update Islamic teachings and adapt them to current developments, while secularization refers to the separation of religion and state. The movement to modernize Islamic thought in Indonesia began in the 19th century as a response to the challenges of the Western world. At this time, Indonesian Muslims began to realize that they were lagging behind the Western world in terms of science, technology and politics. To compensate for this, Muslims began to develop new ideas that could bring Islam into the modern era. Modernization and secularization are two important concepts in the development of Islamic thought in Indonesia Modernization has made Indonesian Muslims think rationally and adapt to current developments, Meanwhile, secularization has enabled Muslims in Indonesia to separate religion and politics and play a more effective role in nation-building.